Valor percebido do luxo: uma comparação entre Austrália e Brasil - Campanario, Paula Marques (2014)
This thesis deals with the influence of cultural differences on luxury goods perceived value, comparing two distinct societies: Brazil and Australia. The research is built on a literature review on luxury consumption. The theoretical model utilized was developed by Wiedmann et al. (2007), which inspired a series of cross-cultural studies. This model is multidimensional, with four latent variables of perceived values: financial, functional, social and individual. Within this tradition, the present research uses multivariate analysis (Partial Least Squares - PLS). An analysis of these variables of each and between the two countries is based in survey data derived from tested scales. Specific changes were made in the financial scale since in other studies this dimension showed no relevance. The results show the soundness of the model utilized, confirming that the theoretical proposition about the relative homogeneity of perceived value in the dimensions of functional, social and individual luxury value in intercultural studies is confirmed. However, as in other studies, it must be pointed out that the weights in each dimension are different, i.e., there are clearly differences between the two countries on detailed analysis of the value constructs such as use, quality, identity, hedonic, conspicuous , prestige and material. Perhaps the most important contribution of this research is that the perceived value of luxury consumption in the financial dimension show to have a relatively important role in the differentiation of the appreciation of values between countries, which requires more research since this insight differs from what most of the literature reveals. Thus, the study achieved its objectives with a review of the literature on luxury, its characteristics as a phenomenon of modern consumption, the major theories of perceived value within a stablished modeling literature and has achieved tangible results through sound statistical analysis. The major conclusion is to further the insights on the prominent role that the perceived value of the financial dimension can have on intercultural studies in this area.